Advanced Encryption Standard (AES) 128 Bit untuk Keamanan Data Internet of Things (IoT) Tanaman Hidroponik - Roiya Ravida; Heru Agus Santoso (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
One method of growing vegetables is to use hydroponics by utilizing water as the medium used. In this era of rapidly developing technology, one of which is Internet of Things (IoT) is a system between computers or objects that can connect and exchange data without requiring interaction, because the data sent is public data, a security system is needed to secure the data sent. Advanced Encryption Standard (AES) 128 bits are used to secure data sent by users or data received by users, using a private key so that data security is maintained. The process of encryption and decryption was carried out through the website using an Arduino Uno microcontroller, SoC version ESP 8266. To adjust the rules for controlling plant needs such as Total Dissolve Solid (TDS), Potential Hydrogen (PH), temperature, and distance, this study uses Sensor2. Database in the research used to facilitate computerized access to assist the process of caring for IoT-based hydroponic plants. The final results have been tested in the encryption decryption process, Avalanche Effect (AE), entropy and Bit Error Ratio (BER). The AE yield 58.01% as highest score, the highest entropy was 6.3566 while all data resulted in BER = 0.